A long‐standing case of desmoplastic fibroblastoma of the face. Issue 7 (11th July 2022) - Singh, Arpita; Ghosh, Snehashish; Shivakotee, Satyapriya; Dhungel, Safal; Raj, A. Thirumal; Patil, Shankargouda
Abstract: The present case report depicts an unusually large desmoplastic fibroblastoma. The diagnosis of the lesion appears to be deceptive clinically. The purpose of this case image is to highlight its size and presenting symptoms, which could easily be mistaken for an odontogenic, salivary gland, or a soft tissue neoplasm. Abstract : The present case report depicts an unusually large desmoplastic fibroblastoma. The diagnosis of the lesion appears to be deceptive clinically. The purpose of this case image is to highlight its size and presenting symptoms, which could easily be mistaken for an odontogenic, salivary gland, or a soft tissue neoplasm.